The Influence of Facilities and Service Quality on Visitor Satisfaction at the 2024 Purnama Bersantai Music Concert - Anhar, Aidil; Parlindungan, Anggiat (Journal of Economics and Social Sciences (JESS), 2025)
The music concert industry in Indonesia continues to experience significant growth, particularly in the city of Medan, which has begun actively developing various local and national-scale entertainment events. One concert that attracted public attention was "Purnama Bersantai 2024", an Indonesian-themed music concert held in the open area of the Lotte Grosir Medan Parking Lot. Although successful in attracting visitors, this concert also drew criticism, particularly related to the inappropriate number of facilities such as toilets and the quality of service staff who were considered unfriendly and unresponsive to complaints. This study aims to analyze the effect of facilities and service quality on visitor satisfaction at the "Purnama Bersantai 2024" concert. This study used a quantitative approach by distributing questionnaires to 97 respondents who attended the event in person. Data were analyzed using multiple linear regression, supplemented by validity and reliability tests, classical assumptions, and hypothesis testing. The results showed that facilities and service quality had a positive and significant effect on visitor satisfaction, both partially and simultaneously. The facility variable has a more dominant influence on visitor satisfaction with a regression coefficient value of 0.069 (sig. 0.001), while service quality has a coefficient value of 0.043 (sig. 0.001). The Adjusted R Square value of 0.539 indicates that 53.9% of the visitor satisfaction variable can be explained by facilities and service quality, while the remaining 46.1% is influenced by other factors outside this study.